Pengembangan LKPD materi himpunan dengan menggunakan pendekatan saintifik berbantuan VBA power point terhadap kemampuan pemahaman matematis siswa SMP - Riyanto, Riyanto; Ristiana, Muhammad Ghiyats (IKIP Siliwangi, 2023)
This study aims to produce LKPD using a scientific approach assisted by vba powerpoint that is appropriate to the stages of development, is valid, practical, and effective on students mathematical understanding abilities on set material. Tis research method is research and development (r&d) with Borg amd Gall stages. This research was conducted at Mts Az-zahra Selacay consisting of 22 students of class VIII and 44 students of class VII. The intruments used are validation sheets, intervies sheets, students questionnaires, and comprehension ability test. The results showed that : (1) the assessment given by the material validator 84% was in the “very valid” category (2) the assessment given by the media validator 85% was in the “very valid” category (3) 72% of students in the limited trial gave practical response and 72,5% of students gave a “practical” response so that this worksheets produk is practical to use (4) the result of the comprehension ability test yo measure effectiveness are in the “effective” category with a percentage of 71%, meaning that this worksheets is effective for use in group learning on the ability to understand mathematics.